2008
DOI: 10.1080/00365520701559003
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxidative stress markers in non-alcoholic steatohepatitis and how it correlates with diet

Abstract: Our data suggest an impaired glutathione metabolism towards an oxidant status in NASH patients, correlating with a higher intake of saturated fat and a lower intake of carbohydrates. Plasmatic concentrations of oxidative stress cellular markers did not translate to hepatic oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 46 publications
2
51
0
5
Order By: Relevance
“…The value for the dietary supplementation of PUFAs in NAFLD has been questioned by findings in a murine model of steatohepatitis, in which n-3 PUFAs failed to prevent the development of steatohepatitis because of accumulation of hepatic lipoperoxides (Larter et al, 2008a). Such effect, however, may be encountered by Sekiya et al, 2003;Capanni et al, 2006;Le Foll et al, 2007;Allard et al, 2008;Machado et al, 2008 340 ANDERSON AND BORLAK combination with other antioxidative strategies, such as treatment with vitamin E. Data from clinical studies had indicated that dietary supplementation with vitamin E in patients with NASH is associated with significant effects on liver transaminase levels and histopathology of NASH, and it may improve serum TNF-␣ levels (Lavine, 2000;Hasegawa et al, 2001;Harrison et al, 2003a;Kugelmas et al, 2003;Sanyal et al, 2004;Dufour et al, 2006;Yakaryilmaz et al, 2007). A combination of vitamin E with phospholipids and silymarin, an extract of milk thistle seed (silybum marianum), resulted in an improvement of hepatic steatosis (as assessed by ultrasonographic scores) and hyperinsulinemia, lowered liver transaminase levels and other indices of liver fibrosis as well as plasma levels of TGF-␤ and TNF-␣ in patients with NAFLD (Loguercio et al, 2007).…”
Section: Other Approachesmentioning
confidence: 86%
“…The value for the dietary supplementation of PUFAs in NAFLD has been questioned by findings in a murine model of steatohepatitis, in which n-3 PUFAs failed to prevent the development of steatohepatitis because of accumulation of hepatic lipoperoxides (Larter et al, 2008a). Such effect, however, may be encountered by Sekiya et al, 2003;Capanni et al, 2006;Le Foll et al, 2007;Allard et al, 2008;Machado et al, 2008 340 ANDERSON AND BORLAK combination with other antioxidative strategies, such as treatment with vitamin E. Data from clinical studies had indicated that dietary supplementation with vitamin E in patients with NASH is associated with significant effects on liver transaminase levels and histopathology of NASH, and it may improve serum TNF-␣ levels (Lavine, 2000;Hasegawa et al, 2001;Harrison et al, 2003a;Kugelmas et al, 2003;Sanyal et al, 2004;Dufour et al, 2006;Yakaryilmaz et al, 2007). A combination of vitamin E with phospholipids and silymarin, an extract of milk thistle seed (silybum marianum), resulted in an improvement of hepatic steatosis (as assessed by ultrasonographic scores) and hyperinsulinemia, lowered liver transaminase levels and other indices of liver fibrosis as well as plasma levels of TGF-␤ and TNF-␣ in patients with NAFLD (Loguercio et al, 2007).…”
Section: Other Approachesmentioning
confidence: 86%
“…Indeed, as in the NASH mice fed with a choline-deficient diet, Yoshida et al [16] reported a more prominent elevation of iPF 2α -Ⅲ in the liver than that in plasma. Machado et al [28] also observed that there was no significant difference in plasma concentrations of 8-OHdG, a DNA oxidation marker, and 4-HNE, a toxic lipid peroxidation product, between patients with NASH and the control. These findings from both animals and human studies suggest a www.wjgnet.com…”
mentioning
confidence: 92%
“…A particular advantage of recent panels is the ability to not only identify hepatic steatosis using a high cut-off value, but also reliably exclude it using a low cut-off value [39,40] . [11] sFas ↑ X Oxidative stress Lipid peroxidation products Ox-LDL ↑ X Kawanaka et al [12] TBARS ↑ X Machado et al [13] MDA ↑ X HNE ↑ X Indicators of altered redox potential…”
Section: Composite Diagnostic Models For Hepatic Steatosismentioning
confidence: 99%